A proposal for a new index to evaluate hospital resource allocation: The case of Italian NHS rationalisation - Domenico Marino; Giuseppe Quattrone (European Research on Management and Business Economics (ERMBE), 2019)
Since the economic crisis of 2008 were growth in health spending has reached unsustainable levels many countries have reduced public spending on health but it is now rising again in Italy (OECD, 2017). This study proposes a new way to use the official indicators for healthcare monitoring in order to assesses the impact by the reform of the Italian National Health Service on the equity access to health care service. A preliminary analysis was performed in order to evaluate geographical hospital resource allocation taking into account both the amount of resources and the intensity of care needed. A second analysis, performed using a two-stage least squares (2SLS) regression model, was addressed to explain geographic lifespan differences between Italian regions. In conclusion, this study attempts to provide an alternative reading to “sector studies”, to highlight more clearly the extent of the “healthcare mobility” phenomenon and the role of the supply structure as a driver of this phenomenon.
Keywords: M11; 650; Health resource